Familial Post-Axial Polydactyly of all Limbs in a Neonate - Victor, Enebeli; Victor, Abhulimen (International Journal of Innovative Research in Medical Science, 2023)
Background: Polydactyly is a common congenital abnormality of the hands and feet characterized by more than five fingers and toes. Polydactyly is amongst the commonest inherited skeletal conditions. Polydactyly can be familial or sporadic. Methods: This article presents a case of familial postaxial polydactyly in a male neonate involving all four limbs seen in our hospital. The mother has history of postaxial polydactyly in both upper limbs consisting only of soft tissue unlike the index patient who has well developed bone on the extra digit. Conclusion: Polydactyly is easily diagnosed at birth however earlier diagnosis during the early antenatal period provides an opportunity for counselling, investigation for syndromic associations or familial gene transmission and planning treatment.